2020
DOI: 10.1519/jsc.0000000000002847
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training Performed With Single and Multiple Sets Induces Similar Improvements in Muscular Strength, Muscle Mass, Muscle Quality, and IGF-1 in Older Women: A Randomized Controlled Trial

Abstract: Cunha PM, Nunes JP, Tomeleri CM, Nascimento MA, Schoenfeld BJ, Antunes M, Gobbo LA, Teixeira D, and Cyrino ES. Resistance training performed with single and multiple sets induces similar improvements in muscular strength, muscle mass, muscle quality, and IGF-1 in older women: A randomized controlled trial. J Strength Cond Res 34(4): 1008–1016, 2020—The purpose of this study was to compare the effects between single set vs. multiple sets of resistance training (RT) on measures of muscular strength, muscle mass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 37 publications
4
63
1
1
Order By: Relevance
“…The SP group obtained especially negative results, showing a significantly different decrease with respect to the active groups (AC vs. SP: p < 0.001 and AP vs. SP: p < 0.05). It has been reported that basal levels of IGF-1 did not change systematically due to resistance training, nor did they differ between young men and older men [57], however these results are in line with those reported in a recent study in which untrained older women were subjected to a strength training programme, improving their IGF-1 levels by 7-10% in twelve intervention weeks, whereas the control group decreased by 2.2% [58]. Likewise, a group of older adults with sarcopenic obesity who engaged in a resistance training programme demonstrated increased muscle strength performance and serum IGF-1 level [26].…”
Section: Insulin-like Growth Factor-1supporting
confidence: 90%
“…The SP group obtained especially negative results, showing a significantly different decrease with respect to the active groups (AC vs. SP: p < 0.001 and AP vs. SP: p < 0.05). It has been reported that basal levels of IGF-1 did not change systematically due to resistance training, nor did they differ between young men and older men [57], however these results are in line with those reported in a recent study in which untrained older women were subjected to a strength training programme, improving their IGF-1 levels by 7-10% in twelve intervention weeks, whereas the control group decreased by 2.2% [58]. Likewise, a group of older adults with sarcopenic obesity who engaged in a resistance training programme demonstrated increased muscle strength performance and serum IGF-1 level [26].…”
Section: Insulin-like Growth Factor-1supporting
confidence: 90%
“…Of the different body regions exposed to RT, 23 studies implemented full-body RT [32][33][34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][52][53][54][55], and 3 implemented lower body RT [9, 31,42]. Thus, only the areas of the body which underwent the RT intervention have been examined by the afore mentioned screening tools.…”
Section: Search Outcomesmentioning
confidence: 99%
“…× repetitions (no.)] [19]. The VL of each week (VL/week) was calculated by summing all the exercise-VL of the eight exercises, obtained in all weekly sessions.…”
Section: Rt Programmentioning
confidence: 99%